Learning from the Dakota: Water and Place - Mona Smith (Open Rivers, 2018)

(untitled)
These videos and audios are from Bdote Memory Map. The deep mapping project created by Allies: media/art is a partnership project with the Minnesota Humanities Center.  The website was created several years ago to help citizens of the area now called Minnesota know where they are, and to learn from the Dakota that this place and the river is not a resource, but rather a relative.